Green tea extract reduces insulin level and folliculogenesis in insulin-resistant PCOS rats model - Irma Maya Puspita; Budi Santoso; Budi Utomo (Majalah Obstetri dan Ginekologi, 2019)
Objectives: Polycystic ovary syndrome (PCOS) is an endocrine disorder with still unknown pathophysiology. Insulin resistance is one of major factors that affect the pathogenesis of PCOS (69%). Green tea has compounds that can be used to improve the condition of insulin resistance, so that folliculogenesis may recur in the case of PCOS.Materials and Methods: The subjects in this study were rats which were divided into 5 groups, consisting of 2 groups serving as a control group (negative and positive) and 3 groups as the treatment group. Each group consisted of 7 experimental animals. Negative control group was given with distilled water for 14 days. Positive control group was given with injections of testosterone propionate 1 mg/100 g BW intramuscularly in the thigh for 28 days to obtain a model of insulin-resistant PCOS and the distilled water was used as therapy. The treatment groups were given wth injections of testosterone propionate 1 mg/100gBW intra-muscularly for 28 days and then treated with green tea extract in doses of each 200 mg/kg, 400 mg/kg, and 800 mg/kg for 14 days. Rats were dissected on day 42 for harvesting the right and left ovary and heart blood sample was taken for examining insulin levels.Results: The results showed that administration of green tea extract on K5 can reduce insulin levels and increase folliculogenesis significantly (significance p <0.05).Conclusion: Green tea extract can reduce insulin levels and increase folliculogenesis in rats. PCOS - Insulin resistance at a dose of 800 mg/kg.